Tinjauan Yuridis Terkait Kewajiban Pelaku Pembangunan Rumah Susun Komersial Dalam Menyediakan Rumah Susun Umum - Narendra, Bagas Putra (NOVUM : JURNAL HUKUM, 2021)
The limitation of the area make construction was carried vertically. One of the ways to resolve is to undertake the construction of public houses flats and commercial houses flats that carried out by the doer of the construction of houses flats. Public houses flats are intended for low-income people while the flats of the commercial house are for profit. However, the provision regarding the area of public flats of at least 20% of the total area of commercial house flats as an obligation of business the doer to construct public flats as stipulated in Article 16 paragraph (2) of the Law on Flats has not provided legal certainty regarding the period for providing public flats for places living Low Income Community (MBR). This study aims to understand and analyzed the determination of a public flat area of at least 20% of the total commercial flat area, as an obligation of the doer in the construction of commercial flats related to Article 16 paragraph (2) of the Law on Flats and to analyze the statutory regulations related to obligations the construction of commercial flat by the doer of the construction of commercial flat to provide legal certainly regarding the period for providing public flats so as not to cause a legal vacuum in regulation and implementation. The research was a normative juridical with data collection through a literature study. A literature study in research was obtained from primary legal materials, secondary legal materials, and non-legal materials. The method used in this research was descriptive and argumentatif techniques. The result showed that the 20% floor test common flats was carried out when the commercial flats were completed, calculated on the total floor area. This determination uses KLB, KDB method, and reviewed according to the RP3KP in each region. In each region, it has not carried out maximum public flats construction, because the Regional Regulation concerning the determination of the floor area of public flats has not been understood by the Regional Government. Legal Certainty related to the provision of public flat commercial flat has not provided legal certainty for its application in the field. Efforts were made to obtain legal certainty by updating Regional Regulations in each region and it is hoped that Real Estate Indonesia (REI) can support the Government’s efforts in providing adequate housing for MBR. Keywords : Houses flats, Obligation, Doer of the construction